2008
DOI: 10.1007/s00442-008-1117-8
|View full text |Cite
|
Sign up to set email alerts
|

Scale-dependent niche axes of arbuscular mycorrhizal fungi

Abstract: Arbuscular mycorrhizal fungi (AMF) are mutualistic with most species of plants and are known to influence plant community diversity and composition. To better understand natural plant communities and the ecological processes they control it is important to understand what determines the distribution and diversity of AMF. We tested three putative niche axes: plant species composition, disturbance history, and soil chemistry against AMF species composition to determine which axis correlated most strongly with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 62 publications
3
53
1
2
Order By: Relevance
“…However, most DNA-based studies have either compared AM fungal diversity between habitats or simply listed species (see Ö pik et al, 2006 for a review). The few attempts to understand processes structuring these communities have been based on spore identification (Fitzsimons et al, 2008), which does not reveal processes regulating fungal communities in planta; or on fungi sampled from a small selection of plant species (Santos et al, 2006;Lekberg et al, 2007;Schechter and Bruns, 2008) or from an environment with minimal variance in soil chemistry (Singh et al, 2008), which will not fully sample all the potential habitats that AM fungi might occupy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most DNA-based studies have either compared AM fungal diversity between habitats or simply listed species (see Ö pik et al, 2006 for a review). The few attempts to understand processes structuring these communities have been based on spore identification (Fitzsimons et al, 2008), which does not reveal processes regulating fungal communities in planta; or on fungi sampled from a small selection of plant species (Santos et al, 2006;Lekberg et al, 2007;Schechter and Bruns, 2008) or from an environment with minimal variance in soil chemistry (Singh et al, 2008), which will not fully sample all the potential habitats that AM fungi might occupy.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, studies using molecular techniques to identify fungi in planta have revealed large differences among the communities of fungi colonizing the roots of coexisting plant species (Vandenkoornhuyse et al, 2003). In addition to host plant effects, soil physical and chemical properties may affect AM fungal communities (Fitzsimons et al, 2008;Liu et al, 2009), implying that AM fungal communities are actually structured by deterministic processes (niche theory). However, the relative importance of these niche and neutral processes in structuring AM fungal communities has yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…The modularity analysis supported this idea. There are indications that AMF diversity and distribution in soils depend on soil properties such as water availability (56), soil texture (57), or soil chemistry (14,15,58). Oehl et al (9), in an extensive study, found that soil type is a key factor determining the composition of the AMF community.…”
Section: Discussionmentioning
confidence: 99%
“…The uniformity of plant cover within croplands may have a homogenizing effect on AM fungal communities. We based this hypothesis on published evidence of the selective influence of plants on extraradical AM fungal growth (14) and on the structure of AM fungal communities in soil (76,77). Host plants have a large influence in shaping AM fungal communities in soils (78,79).…”
Section: Discussionmentioning
confidence: 99%